Pengaruh Audit Tenure, Kepemilikan Manajerial, dan Ukuran Perusahaan terhadap Integritas Laporan Keuangan - Galingging, Elvita Sabat Uly Vera; Yulianto, Eko (Penerbit Goodwood, 2024)
Purpose: This study examined the impact of audit tenure, managerial ownership, and company size on the integrity of financial statements. Methodology: The sample was selected using purposive sampling, resulting in 29 companies and 77 data points from transportation and logistics companies listed on the Indonesia Stock Exchange during the period 2020-2022. Secondary data from the annual reports were analyzed using multiple linear regression. Results: Company size affects the integrity of financial statements, whereas audit tenure and managerial ownership do not. Limitations: The study is limited by measuring audit tenure as the number of years a Public Accounting Firm has engaged with a client, going back up to six years. Additionally, only one measurement tool–accounting conservatism–was used. Contribution: The findings are expected to enhance the understanding of financial statement integrity for both internal users, such as management, and external users, such as creditors and investors, aiding in making informed decisions. Furthermore, this study contributes to the literature by expanding the determinants of financial statement integrity in transportation and logistics companies. Novelty: This study addresses gaps in previous research, employs STATA software, focuses on the transportation and logistics sector, and covers the most recent period.